Pemanfaatan Teknologi Kecerdasan Buatan Dalam Meningkatkan Prestasi Akademik Siswa Sekolah Menengah Atas Di SMA Negeri 9 Bengkulu - Ahmad Asyhari; Rizka Tri Alinse; Fahrul Ikram Nizar; Yance Pransiska; Muhamad Bitang Firdaus (Universitas Dehasen Bengkulu, 2024)
The development of information and communication technology has significantly influenced the education sector, particularly through the utilization of Artificial Intelligence (AI). This technology has great potential to improve the quality of learning and students' academic performance. This community service activity aims to increase students' understanding of the basic concepts of artificial intelligence and its application in supporting the learning process at SMA Negeri 9 Bengkulu. The implementation method used lectures, presentations, and discussion sessions with participants. The activity stages included an initial stage consisting of introductions and explanation of activity objectives, a core stage involving the presentation of materials related to artificial intelligence technology, and a final stage consisting of discussions and question-and-answer sessions. The results indicate that students gained better understanding of the development of artificial intelligence technology and its benefits in supporting academic activities. Furthermore, this activity increased students’ awareness of the importance of using technology positively in the learning process in the digital era.